The wizard of oz - Baum, Frank (OUP Oxford Karachi, 2005)
Dorothy and her little dog, Toto, are carried by a cyclone from her aunt and uncle's house in Kansas. When they come down, they find themselves in the land of Oz. There Dorothy begins an exciting journey with her new friends. They want to go and see the wonderful Wizard of Oz in the Emerald City. Only he can give them what they want. Will Dorothy be able to go home to Kansas? Who is the Wizard of Oz? Can he help Dorothy and her friends?